Physoxia alters human mesenchymal stem cell secretome - Merkhan, Marwan M; Shephard, Matthew T; Forsyth, Nicholas R (Journal of tissue engineering, 2021)
The human mesenchymal stem cell (hMSC) secretome has pleiotropic effects which underpin their therapeutic potential. hMSC serum-free conditioned media (SFCM) has been determined to contain a variety of cytokines with roles in regeneration and suppression of inflammation. Physiological oxygen (physoxia) has been demonstrated to impact upon a number of facets of hMSC biology and we hypothesized that the secretome would be similarly modified. We tested a range of oxygen conditions; 21% O2 (air oxygen (AO)), 2% O2 (intermittent hypoxia (IH)) and 2% O2 Workstation (physoxia (P)) to evaluate their effect on hMSC secretome profiles. Total protein content of secretome was upregulated in IH and P (>3 fold vs AO) and IH (>1 fold vs P). Focused cytokine profiling indicated global upregulation in IH of all 31 biomolecules tested in comparison to AO and P with basic-nerve growth factor (bNGF) and granulocyte colony-stimulating factor (GCSF) (>3 fold vs AO) and bNGF and Rantes (>3 fold vs P) of note. Similarly, upregulation of interferon gamma-induced protein 10 (IP10) was noted in P (>3 fold vs AO). Interleukin-2 (IL2) and Rantes (in AO and P) and adiponectin, IL17a, and epidermal growth factor (EGF) (in AO only) were entirely absent or below detection limits. Quantitative analysis validated the pattern of IH-induced upregulation in vascular endothelial growth factor (VEGF), placental growth factor-1 (PIGF1), Tumor necrosis factor alpha (TNFa), IL2, IL4, and IL10 when compared to AO and P. In summary, modulation of environmental oxygen alters both secretome concentration and composition. This consideration will likely impact on delivering improved mechanistic understanding and potency effects of hMSC-based therapeutics.